Broadcasting Queer Feminisms: Lesbian and Queer Women Programming in Transnational, Local, and Community Radio - Copeland, Stacey (Journal of Radio & Audio Media, 2018)
Notable radio scholars including Christine Ehrick, Phylis A. Johnson, and Caroline Mitchell have explored critical challenges of gender and sexuality radio research and its importance in relation to communities. A major issue faced in studying the early years of women’s history in broadcast is the ephemeral nature of the medium as many of the voices are lost in the ether, unrecorded or once deemed inessential to archive. Web-based radio and podcast archives provide renewed avenues for listening to lesbian and queer women’s radio across transnational borders yet many long running shows in Canada such as The Lesbian Show on Vancouver Co-Op Radio have only recently begun to surface as digital collections. As personal and institutional archives of lesbian and queer women radio begin to reach a public audience, analysis of radio works across decades of LGBTQ2+ activism and feminisms must be traced to understand the role of radio and digital radiogenic media in creating space and identity for queer activism. A turn to the past brings forward questions of analog and digital futures for radio and podcasting space as place to construct and shape queer and especially lesbian communities and identities in the North American broadcasting industry. Through research of notable live and pre-produced content including Dykes on Mykes on CKUT 90.3 FM, and The Lesbian Show on Vancouver Co-Op Radio, this work offers an exploration of radio and radiogenic media’s role in creating sonic space for queer and feminist subjectivities.